Au@p4VP core@shell pH-sensitive nanocomposites suitable for drug entrapment - Clara-Rahola, Joaquim; Moscoso, Ana; Ruiz-Muelle, Ana Belen; Laurenti, Marco; Formanek, Petr; Lopez-Romero, Juan M.; Fernandez, Ignacio; Fernando Diaz, J.; Rubio-Retama, Jorge; Fery, Andreas; Contreras-Caceres, Rafael (Journal of Colloid and Interface Science, 2018)
We synthesize and characterize pH-responsive hybrid nanocomposites with SERS and drug loading applications. This colloidal system is structured by spherical 50 nm Au cores individually coated by a pH-sensitive shell of poly4-vinylpyridine (Au@p4VP). The synthesis of these hybrid nanocomposites is performed in two steps, a first one involves the fabrication of vinyl-functionalized Au nanoparticles, and a second one includes the controlled overgrowth of a p4VP shell by free radical polymerization. As a result, Au@p4VP hybrid systems with a mean diameter ranging from 150 to 57 nm are obtained upon varying the monomer concentration at synthesis. Au@p4VP nanocomposite exhibits pH-response capabilities, confirmed by cryo-TEM analysis, Small Angle X-ray Scattering (SAXS) and Zeta Potential (ZP) measurements at different pH conditions. The Au@p4VP particles also display a controllable swelling response, which depends on the cross-linker density within the polymer. This swelling capability is analyzed by Dynamic Light Scattering (DLS), and UV–vis spectroscopy at different pHs. The pH-responsive capability is here exploited for the chemical entrapment of doxorubicin hydrochloride (Dox) into the polymer network. The presence of this molecule is resolved by Surface Enhanced Raman Spectroscopy (SERS) measurements. The entrapment efficiency of Dox by the Au@p4VP system is determined via NMR spectroscopy of the supernatants.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Cryo-TEM; Gold nanoparticles; Nanocomposite system; SERS; Stimuli-responsive